2011
DOI: 10.1063/1.3557501
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of ambient sensitive atomic layer deposited lanthanum aluminates by annealing and in situ capping

Abstract: Articles you may be interested inEffect of annealing and electrical properties of high-κ thin films grown by atomic layer deposition using carboxylic acids as oxygen source

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This behavior may be explained by a gradually increasing contribution of the CVD component. This may be due to larger hygroscopicity for lower density (and/or higher C contamination) Gd 2 O 3 , similar to what has been observed for LaAlO 3 . If one assumes that the CVD component deposits a lower density and/or higher C-contaminated layer, there may exist some intrinsic positive feedback for the CVD component, leading to deteriorating film quality and increasing WiWNU as the deposition progresses.…”
Section: Resultsmentioning
confidence: 58%
“…This behavior may be explained by a gradually increasing contribution of the CVD component. This may be due to larger hygroscopicity for lower density (and/or higher C contamination) Gd 2 O 3 , similar to what has been observed for LaAlO 3 . If one assumes that the CVD component deposits a lower density and/or higher C-contaminated layer, there may exist some intrinsic positive feedback for the CVD component, leading to deteriorating film quality and increasing WiWNU as the deposition progresses.…”
Section: Resultsmentioning
confidence: 58%
“…This discrepancy can be resolved if the vibrational modes did not stem from the formation of oxycarbonates during deposition, [53] but from reactive surface (or near surface) adsorption of CO 2 or carboxyl groups from the atmosphere, as the low-temperature-grown ALD films show low density. [54] This interpretation is further upheld by the post-deposition anneal behavior of the low-temperaturegrown ALD films at 400 8C in an inert N 2 atmosphere. The analysis showed that ALD films deposited at 140 8C were found to show a measurable decrease in both mass and thickness with a concomitant gain in density (À3% for mass and thickness and þ4% for density) due to outgassing of impurities and film shrinkage.…”
mentioning
confidence: 93%
“…Peak IV, related to La(OH) x , may come from the hygroscopicity of the La 2 O 3 [ 16 ]. After high temperature annealing treatments, significant decrease in the intensity of peak IV could be observed, indicating the reduction of hydroxyl groups [ 17 ]. It is found that the intensity of Peak V shows a more obvious increase when the annealing treatment was carried out in O 2 ambient compared with that in N 2 or vacuum ambient, indicating that more Si–O–Si bonds were formed during the RTA process in O 2 ambient.…”
Section: Resultsmentioning
confidence: 99%